Una voz poético-métrica de Cervantes: aquelindo en El rufián dichoso - Fernández Hoyos, Sonia; Fernández de la Torre, José Luis (El Colegio de México, 2018)
El rufián dichoso  is not merely a hagiography of the student-valentón Lugo in Seville and his definitive metamorphosis into Friar Cristóbal de la Cruz in Mexico. It is a play that presents a number of technical problems, one of those involving the aquelindo, the poetic composition sung and danced at the beginning of the play. The present article proposes that it here takes the form of a romance-jácara composed of two quintillas (five-line stanzas) and five redondillas (quatrains), and that it should not be confused with the traditional perqué, as previously has been suggested.